LITHOLOGY UNITS WANAJAYA AREA AND SURROUNDING, BUAHDUA SUBDISTRICT, SUMEDANG DISTRICT, WEST JAVA PROVINCE - Ganjar Gani, Reza Moh; Firmansyah, Yusi; Arfiansyah, Kurnia; Efendi, Tri Septanto; Rodhiya, Azzam Robbi (Journal of Geological Sciences and Applied Geology, 2025)
The research site is located in Wanajaya Village, Buahdua Subdistrict, Gunung Kidul Regency, West Java Province. Accessibility to the research location using a motorbike. The purpose of this study is to determine the geological conditions of the study area in terms of lithological units and stratigraphic order. The lithological unit of the study area is divided into 4 lithological units, namely the Mudstone Unit, the Andesite Intrusion Unit, the Volcanic Breccia Unit and the Andesite Lava Unit, namely the naming of rock units based on observable physical characteristics, including rock type, uniformity of lithological symptoms and stratigraphic position. The geological history of the first research site in the Late Miocene to Early Pliocene time was deposited by the mudstone unit. In the late Pliocene to Pleistocene volcanism activity occurred due to the displacement of the volcanic centre from the south to the centre of Java (Martodjojo, 1984) which caused the formation of the wanajaya fold and continued with the formation of the wanajaya ascending fault. As a result of the weak fault zone, the andesite intrusion unit appeared, which was the beginning of the activity of the old volcano. In Pleistocene time, namely deposition of Volcanic Breccia Unit and continued by the deposition of andesite lava unit due to volcanism activity of Tampomas volcano issued pyroclastic material.